TRANSFORMATION OF IDEOLOGY UKRAINIAN NATIONALISM IN LIGHT OF DECISIONS OF THE THIRD EXTRAORDINARY GREAT ASSEMBLY Of OUN - Максимець, Б. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Transformation ideology of ukrainian nationalism in light of decisions of the Third extraordinary great assembly of OUN in 1943 is traced and its impact on the further development of the ukrainian nationalist movement is determined.